2019
DOI: 10.1029/2019jb018826
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Omphacite as a Function of Water Content and Implications for High Conductivity Anomalies in the Dabie‐Sulu UHPM Belts and Tibet

Abstract: Magnetotelluric surveys revealed high‐conductivity layers in the lower crust beneath Tibet and in the shallow part of the upper mantle relevant to continental collision extending to the Dabie‐Sulu ultrahigh‐pressure metamorphic (UHPM) belts of eastern China, which have been interpreted by the presence of aqueous fluids/partial melts or hydrous phases. However, these explanations are not consistent with their petrological features and seismic properties. Hydrogen‐bearing omphacite could be a probable candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 74 publications
(170 reference statements)
7
15
0
Order By: Relevance
“…2b for hydrogen diffusion in (Mg,Fe) 2 SiO 4 ringwoodite, the experimental data reported by Kudo et al (2006) are comparable with that calculated by the cB model (Zhang, 2012). Sun et al (2015) reported a hydrogen self-diffusion coefficient in Fe-bearing ringwood- (Hae et al, 2006); Z12 (Zhang, 2012); S18 (Sun et al, 2018); K06 (Kudo et al, 2006); K04 (Kubo et al, 2004); H09 (Holzapfel et al, 2009); S04 (Shimojuku et al, 2004); S09 (Shimojuku et al, 2009); S10 (Shimojuku et al, 2010); Z11 (Zhang et al, 2011); Z15a (Zhang and Shan, 2015a); Z15b (Zhang and Shan, 2015b); Z19b (B. H. Zhang et al, 2019b); Z21 (Zhang et al, 2021).…”
Section: Ringwooditesupporting
confidence: 73%
See 4 more Smart Citations
“…2b for hydrogen diffusion in (Mg,Fe) 2 SiO 4 ringwoodite, the experimental data reported by Kudo et al (2006) are comparable with that calculated by the cB model (Zhang, 2012). Sun et al (2015) reported a hydrogen self-diffusion coefficient in Fe-bearing ringwood- (Hae et al, 2006); Z12 (Zhang, 2012); S18 (Sun et al, 2018); K06 (Kudo et al, 2006); K04 (Kubo et al, 2004); H09 (Holzapfel et al, 2009); S04 (Shimojuku et al, 2004); S09 (Shimojuku et al, 2009); S10 (Shimojuku et al, 2010); Z11 (Zhang et al, 2011); Z15a (Zhang and Shan, 2015a); Z15b (Zhang and Shan, 2015b); Z19b (B. H. Zhang et al, 2019b); Z21 (Zhang et al, 2021).…”
Section: Ringwooditesupporting
confidence: 73%
“…2a). In addition, the activation energy (∼ 113 kJ/mol) obtained by Zhang et al (2021) was much lower than that (229-289 kJ/mol) determined by Holzapfel et al (2009) and Zhang and Shan (2015a).…”
Section: Wadsleyitementioning
confidence: 56%
See 3 more Smart Citations